L-Carnitine Is Involved in Hyperbaric Oxygen-Mediated Therapeutic Effects in High Fat Diet-Induced Lipid Metabolism Dysfunction - Junhua Yuan; Qixiao Jiang; Limin Song; Yuan Liu; Manwen Li; Qian Lin; Yanrun Li; Kaizhen Su; Zhengye Ma; Yifei Wang; Defeng Liu; Jing Dong (Molecules, 2020)
Lipid metabolism dysfunction and obesity are serious health issues to human beings. The current study investigated the effects of hyperbaric oxygen (HBO) against high fat diet (HFD)-induced lipid metabolism dysfunction and the roles of L-carnitine. C57/B6 mice were fed with HFD or normal chew diet, with or without HBO treatment. Histopathological methods were used to assess the adipose tissues, serum free fatty acid (FFA) levels were assessed with enzymatic methods, and the endogenous circulation and skeletal muscle L-carnitine levels were assessed with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Additionally, western blotting was used to assess the expression levels of PPARα, CPT1b, pHSL/HSL, and UCP1. HFD treatment increased body/adipose tissue weight, serum FFA levels, circulation L-carnitines and decreased skeletal muscle L-carnitine levels, while HBO treatment alleviated such changes. Moreover, HFD treatment increased fatty acid deposition in adipose tissues and decreased the expression of HSL, while HBO treatment alleviated such changes. Additionally, HFD treatment decreased the expression levels of PPARα and increased those of CPT1b in skeletal muscle, while HBO treatment effectively reverted such changes as well. In brown adipose tissues, HFD increased the expression of UCP1 and the phosphorylation of HSL, which was abolished by HBO treatment as well. In summary, HBO treatment may alleviate HFD-induced fatty acid metabolism dysfunction in C57/B6 mice, which seems to be associated with circulation and skeletal muscle L-carnitine levels and PPARα expression.